1986
DOI: 10.1002/1097-0142(19860515)57:10<1986::aid-cncr2820571017>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Semen analysis in Hodgkin's disease before the onset of treatment

Abstract: A spermogram was performed before treatment in 57 young patients with Hodgkin's disease. The mean results were normal, and similar to those reported in fertile populations. Nineteen patients had an abnormal spermogram; 12 of these men had had fever recently or were febrile at the time of the exam. When the temperature was below 38.5 degrees C, there was only asthenospermia. With a higher temperature, semen anomalies were more severe, with oligoasthenospermia or even azoospermia. Only five febrile men had a nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
3

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 12 publications
1
21
0
3
Order By: Relevance
“…Therefore, it is recommended to cryopreserve patients' sperm before the start of intensive chemotherapy. There are several reports on the sperm production impairment in patients with untreated Hodgkin lymphoma [12,13]. In our study, two untreated patients with AML showed sperm abnormalities.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…Therefore, it is recommended to cryopreserve patients' sperm before the start of intensive chemotherapy. There are several reports on the sperm production impairment in patients with untreated Hodgkin lymphoma [12,13]. In our study, two untreated patients with AML showed sperm abnormalities.…”
supporting
confidence: 46%
“…The etiology of dyspermia in the two patients remains unknown. Fever or an immune-mediated mechanism associated with leukemia may deteriorate sperm production [12,13]. When sperm cryopreservation is planned, we should pay attention to the possibility of the sperm production impairment in untreated patients.…”
mentioning
confidence: 99%
“…29 Compared to previous studies in patients with Hodgkin's lymphoma, our data showed better sperm quality than in some analyses, 6,30 but worse quality than in others. 7,31,32 Our study was, however, based on data from by far the largest series studied up date; this offered not only a more reliable estimation of sperm quality but also the opportunity to study factors influencing sperm quality. Neither of the two groups 5,32 that tried to analyze the influence of B-symptoms and fever on sperm quality before treatment found a significant difference between patients with or without these manifestations, most probably due to limited sample sizes (92 and 94 patients, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Data from patients with Hodgkin's lymphoma hint that before treatment such patients have lower sperm counts and reduced sperm motility compared to healthy subjects, 4,5 but data from large series of patients are lacking; the largest series studied thus far comprised 212 patients. 6 The cause of the diminishment in semen quality is not completely understood and has been attributed to fever, poor performance, psychological factors 7,8 or even immune-mediated mechanisms. 9 For many years gonadal toxicity has been studied in trials by the European Organization for Research and Treatment of Cancer (EORTC) Lymphoma Group and the Groupe d'Étude des Lymphomes de l'Adulte (GELA).…”
Section: Introductionmentioning
confidence: 99%
“…Чаще нарушения сперма-тогенеза наблюдаются при лимфоме Ходжкина (ЛХ), неходжкинской лимфоме (НХЛ), остром лимфобласт-ном лейкозе (ОЛЛ), опухолях яичка [9,10] и проявля-ются снижением показателей спермограммы [11][12][13]. По разным данным, инициальные нарушения сперма-тогенеза встречаются от 25 до 70 % при ЛХ и других опухолях [6,[14][15][16][17].…”
Section: влияние опухолевого процесса на сперматогенезunclassified